"A Quintessentially American Thing?": The Unexpected Link between Individualistic Values and the Sense of Personal Control. (November 2016) - Narisada, Atsushi; Schieman, Scott
A popular image of Americans is that they are among the most individualistic people on the planet. This long-standing myth has informed theorizing about the sense of control and its relevance for stress and mental health. Prior claims have suggested that differences based on individualistic and collectivistic values contribute to group differences in the sense of control. We analyze data from the World Values Survey to test this hypothesis, focusing on a comparison of Americans and individuals in East Asian societies. Findings demonstrate that Asians report lower perceived control than Americans—but adjustments for individualistic values do not explain these differences. The positive association between individualistic values and perceived control is stronger among Asians compared to Americans. Perceived control is associated most strongly with subjective well-being for Americans, but individualistic values do not explain the differences. Our observations question claims that Americans gain more from individualistic values while Asians are sanctioned for them. Given its significance for stress and mental health, it is essential to document social patterns in the levels and effects of perceived control. We contribute to that effort by uncovering unexpected patterns that challenge the claim that individualistic values—and their benefits for control—are a quintessentially American thing.